APPLIED POHLIG-HELLMAN ALGORITHM IN THREE-PASS PROTOCOL COMMUNICATION - Rahim, Robbi (Journal of Applied Engineering Science, 2018)
Three-pass Protocol is a method or technique that can be used by 2 (two) sender and recipient of the message to communicate with each other using XOR function, the problem that occurs is when the communication process there is parties who can know the messages sent from the sender to the recipient. To solve the problem we need an algorithm in this case Pohlig-Hellman algorithm, the use of Pohlig-Hellman algorithm on Three-pass Protocol ensures the security of messages sent by the sender to the receiver because each sender and receiver uses keys p, e, and d which is a number random and d is the inverse modulo of p and e of the sender and receiver, the results of this research suggest that it is impossible for the attacker or cryptanalyst to know the correct message quickly despite having adequate computer resources
Keywords: Little Theorem Fermat; Sieve of Eratosthenes; Pohlig-Hellman Algorithm; Three-Pass Protocol; Recivers; Algorithms